Detection of alleles associated with resistance to chemical insecticide in the malaria vector Anopheles arabiensis in Santiago, Cabo Verde - Derciliano Lopes da Cruz; Marcelo Henrique Santos Paiva; Duschinka Ribeiro Duarte Guedes; Joana Alves; Lara Ferrero Gómez; Constância Flávia Junqueira Ayres (Malaria Journal, 2019)
Abstract Background Mosquitoes of the Anopheles gambiae complex are the main malaria vectors worldwide. Due to the lack of a vaccine to prevent malaria, the principal way to reduce the impact of this disease relies on the use of chemical insecticides to control its vectors. However, the intensive use of such compounds has led to the emergence of insecticide resistance in several Anopheles populations in Africa. This study aimed to investigate the presence of resistance alleles in an Anopheles arabiensis population from the City of Praia, capital of the Archipelago Cabo Verde, one of the countries on the World Health Organization list of countries that are on a path to eliminate local transmission of malaria. Methods Larvae from the Anopheles genus were collected using a one-pint dipper in three areas of City of Praia. Larvae were fed and maintained until the emergence of adult mosquitoes, and these were morphologically identified. In addition, molecular identification was performed using IGS markers and all An. arabiensis samples were subjected to PCR to screen for mutations associated to resistance in the Ace-1, Na v and GSTE2 genes. Results From a total of 440 mosquitoes collected, 52.3% were morphologically identified as An. gambiae sensu lato (s.l.) and 46.7% as Anopheles pretoriensis. The molecular identification showed that 100% of the An. gambiae s.l. were An. arabiensis. The mutations G119S in the Ace-1 gene and L119F in the GSTE2 gene were screened but not found in any sample. However, sequencing analysis for GSTE2 revealed the presence of 37 haplotypes, 16 polymorphic sites and a high genetic diversity (π = 2.67). The L1014S mutation in the Na v (voltage-gated sodium channel gene) was detected at a frequency of 7.3%. Conclusion This is the first study to investigate the circulation of insecticide resistance alleles in An. arabiensis from Cabo Verde. The circulation of the L1014S allele in the population of An. arabiensis in the city of Praia suggests that pyrethroid resistance may arise, be quickly ...